IMPROVEMENT OF THE SUBJECT "TECHNICAL CREATIVITY AND DESIGN" FROM A PRACTICAL AND METHODOLOGICAL ASPECT WITH THE HELP OF MOBILE APPLICATIONS (International journal of artificial intelligence, 2025)
This study introduces a new methodology for teaching the subject “Technical Creativity and Design” in higher and secondary specialized educational institutions through mobile application development projects. The proposed approach guides students through all stages of creative engineering activity, including problem identification, formulation of technical requirements, design development, and registration of the final product as a utility model. The methodology integrates project-based learning, TRIZ elements, and Agile principles. A pilot implementation conducted in five technical universities in Uzbekistan demonstrated significant improvements, with students’ creative engagement and patent activity increasing by 2.5–3 times.